Integration of Lightweight Foam Concrete Roof, Moving-Air-Cavity, and Solar-Powered Fans for Attic Temperature Reduction - Yew, Ming Chian; Yew, Ming Kun; Ho, Mun Ling; Saw, Lip Huat (Frontiers in Built Environment, 2021)
This paper presents a novel cool roof technology system that promotes both passive and active cooling methods in reducing the attic temperature of the building. The project aimed to evaluate the effect of various roof model designs on the heating load to establish the capacity of a cooling roof system by maintaining the thermal comfort level for occupants in the buildings. There are four main components in constructing the cool roof models: (1) metal deck roof, (2) lightweight foam concrete roof, (3) moving-air-cavity (MAC) ventilation and (4) solar-powered fan. Four small-scale cool roof models were built to evaluate the performance of each cool roof designs. The performances of the roof surface and attic temperatures of each designed cool roof models were compared with the conventional metal deck roof. The roof models were conducted indoors by using halogen spotlights. The result of the Roof Design IV with the integration of lightweight foam concrete, MAC and solar-powered fans has effectively reduced the attic temperature by 6.0 °C as compared to the normal roof model (Roof Design I). As a result, this integrated cool roof design comprises the ability to enhance the comfortability of occupants towards long-term sustainable development with the utilization of renewable energy to protect and improve the natural environment.